Mis-splicing drives loss of function of p53E224D point mutation - Ian C. Lock; Nathan H. Leisenring; Warren Floyd; Eric S. Xu; Lixia Luo; Yan Ma; Erin C. Mansell; Diana M. Cardona; Chang-Lung Lee; David G. Kirsch (PLoS ONE, 2025)
Background The tumor suppressor p53 (Trp53), also known as p53, is the most commonly mutated gene in cancer. Canonical p53 DNA damage response pathways are well characterized and classically thought to underlie the tumor suppressive effect of p53. Challenging this dogma, mouse models have revealed that p53-driven apoptosis and cell cycle arrest are dispensable for tumor suppression. Here, we investigated the inverse context of a p53 mutation predicted to drive the expression of canonical targets but is detected in human cancer. Methods We established a novel mouse model with a single base pair mutation (GAG>GAT, p53E221D) in the DNA-Binding domain that has wild-type function in screening assays, but is paradoxically found in human cancer in Li-Fraumeni syndrome. Using mouse p53E221D and the analogous human p53E224D mutants, we evaluated expression, transcriptional activation, and tumor suppression in vitro and in vivo. Results Expression of human p53E224D from cDNA translated to a fully functional p53 protein. However, p53E221D/E221D RNA transcribed from the endogenous locus is mis-spliced resulting in nonsense-mediated decay. Moreover, fibroblasts derived from p53E221D/E221D mice do not express a detectable protein product. Mice homozygous for p53E221D exhibited increased tumor penetrance and decreased life expectancy compared to p53WT/WT animals. Conclusions Mouse p53E221D and human p53E224D mutations lead to splice variation and a biologically relevant p53 loss of function in vitro and in vivo.